Efficacy and adverse effects of sotalol in adults with congenital heart disease. (1st January 2019) - Moore, Benjamin M.; Cordina, Rachael L.; McGuire, Mark A.; Celermajer, David S.
Abstract: Introduction: Adults with congenital heart disease (CHD) are predisposed to arrhythmias, which can often be refractory to medical therapy. Sotalol is an attractive alternative antiarrhythmic to amiodarone in this younger patient population, given the latter's toxicity profile, but it may have proarrhythmic effects. We therefore aimed to assess the efficacy and safety of sotalol in adults with CHD. Methods: We retrospectively assessed our adult CHD database for all patients ≥16 years old, with moderate to highly complex defects, who were prescribed sotalol between 2000 and 2017. Efficacy in treating the clinical arrhythmia was assessed as complete, partial or failure. Adverse effects, including proarrhythmia, were documented. Results: Sotalol was prescribed in 82 of 902 adult CHD patients reviewed (9%). The mean age at sotalol commencement was 31.8 ± 13.1 years, with a median time on sotalol of 2.8 years. The average prescribed dose was 122 ± 51 mg/daily. Sotalol was completely effective in 48% (n = 39), partially effective in 46% (n = 38) and failed to control the clinical arrhythmia in 6% (n = 5). Fifteen patients (18%) discontinued sotalol due to a side effect, most commonly fatigue or dyspnoea. No episodes of torsades de pointes or sudden cardiac death were observed. Significant bradycardia related to sotalol occurred in 13% (n = 11, with permanent pacing implemented in 4), and was associated with Fontan anatomy. Conclusions: In moderate to highly complex adult CHD, sotalol was reasonably effective and safe in low doses. Side effects limiting treatment were typically non-life-threatening, with significant bradycardia related to sotalol more likely in Fontan patients. Highlights: Sotalol, in adult congenital heart disease, is reasonably effective and safe at low doses. Side effects are typically non-life-threatening. No cases of sudden cardiac death or torsades de pointes were observed in over 400 patient years of drug therapy. Significant bradycardia on sotalol is more common in Fontan patients.